Development of iron-vitamin multilayer encapsulates using 3 fluid nozzle spray drying. (16th April 2023) - Nimbkar, Shubham; Leena, M. Maria; Moses, J.A.; Anandharamakrishnan, C.
Graphical abstract: Highlights: Formation of core–shell microencapsulates using 3-FN spray drying. Comparison of novel core–shell and conventional matrix-type encapsulates. The effect of pH of whey protein on colour of microencapsulates is evident. Increased encapsulation efficiency of iron in core–shell encapsulates. Slower release of iron by core–shell encapsulates compared to matrix-type ones. Abstract: Considering the growing concern of iron and folic acid deficiency, encapsulation of these nutrients and fortification into foods is emerging as an effective counter-strategy. The present work focuses on a scalable approach for the production of iron, ascorbic acid, and folic acid core–shell encapsulates using novel 3-fluid nozzle (3FN) spray drying with whey protein as core and either pectin or hydroxypropyl methylcellulose (HPMC) as shell polymers. The effect of shell formation was observed by comparing core–shell encapsulates with conventional 2-fluid nozzle (2FN) encapsulates. Also, the effect of pH of whey protein on the color of encapsulates is noteworthy; reducing the pH to 4.0 significantly improved the lightness value (52.91 ± 0.13) when compared with the encapsulates with native pH (38.91 ± 0.58). Furthermore, sample with pectin as shell polymer exhibited fair flowability with lowest values of Hausner ratio (1.25 ± 0.04) and Carr's index (20.06 ± 2.71) and highest encapsulation efficiency for folic acid (86.07 ± 5.24%). Whereas, encapsulates having HPMC as shell polymer showed highest lightness value (60.80 ± 0.32) and highest encapsulation efficiency for iron (87.28 ± 4.15%). The formation of core–shell structure was confirmed by evaluation of the surface composition which showed reduced amine bonds and increased aliphatic and carbonyl bonds in the encapsulates prepared by 3FN spray drying. The encapsulates prepared without adjusting whey protein pH showed the least release (∼51 % in 24 h) and bioaccessibility (∼56%) of iron indicating the iron-whey protein complex formation. Based on appearance, smooth surface morphology, flowability, and release behavior, a combination of whey protein and pectin is recommended for co-encapsulation of iron, folic acid and ascorbic acid.